Manual de procesos para el mejoramiento del servicio de logística de atención al cliente en la empresa importadora castro “Quevedo” en el periodo 2023 - Zamora Montenegro, Adriana Marena (2024)
Importadora Castro, a company with more than 25 years of experience, faces challenges in its merchandise delivery service in the Quevedo canton, manifested by recurring delays, errors in orders and a decrease in customer satisfaction. To address this problem, the company has decided to implement a Process Manual that will not only address each phase of merchandise delivery, but will also be used for the continuous improvement of logistics processes. The overall objective is to improve the efficiency and quality of customer service logistics service to increase customer satisfaction and strengthen competitiveness in the market. The implementation of the manual will provide clear guidelines, standardization, reduction of errors and faster and more accurate delivery, which will improve customer satisfaction and the reputation of Importadora Castro "Quevedo" in the market. In addition, the manual will allow adaptability and continuous improvement of processes, promoting an organizational culture oriented towards efficiency and innovation. This strategy not only addresses operational challenges, but also seeks to raise service quality and competitiveness in the market.